Landscape ecology of two species of declining grassland sparrows - Herse, Mark Richard (Kansas State University, 2017)
Species extinctions over the past two centuries have mainly been caused by habitat destruction. Landscape change typically reduces habitat area, and can fragment contiguous habitat into remnant patches that are more subject to anthropogenic disturbance. Furthermore, changes in the landscape matrix and land-use intensification within remaining natural areas can reduce habitat quality and exacerbate the consequences of habitat loss and fragmentation. Accordingly, wildlife conservation requires an understanding of how landscape structure influences habitat selection. However, most studies of habitat selection are conducted at fine spatial scales and fail to account for landscape context. Temperate grasslands are a critically endangered biome, and remaining prairies are threatened by woody encroachment and disruptions to historic fire-grazing regimes. Here, I investigated the effects of habitat area, fragmentation, woody cover, and rangeland management on habitat selection by two species of declining grassland-obligate sparrows: Henslow’s Sparrows (Ammodramus henslowii) and Grasshopper Sparrows (A. savannarum). I conducted >10,000 bird surveys at sites located throughout eastern Kansas, home to North America’s largest remaining tracts of tallgrass prairie, during the breeding seasons of 2015 and 2016. I assessed the relative importance of different landscape attributes in determining occurrence and within-season site-fidelity of Henslow’s Sparrows using dynamic occupancy models. The species was rare, inhabited <1% of sites, and appeared and disappeared from sites within and between seasons. Henslow’s Sparrows only settled in unburned prairie early in spring, but later in the season, inhabited burned areas and responded to landscape structure at larger scales (50-ha area early in spring vs. 200-ha during mid-season). Sparrows usually settled in unfragmented prairie, strongly favored Conservation Reserve Program (CRP) fields embedded within rangeland, avoided trees, and disappeared from hayfields after mowing. Having identified fragmentation as an important determinant of Henslow’s Sparrow occurrence, I used N-mixture models to test whether abundance of the more common Grasshopper Sparrow was driven by total habitat area or core habitat area (i.e. grasslands >60 m from woodlands, croplands, or urbanized areas). Among 50-ha landscapes containing the same total grassland area, sparrows favored landscapes with more core habitat, and like Henslow’s Sparrows, avoided trees; in landscapes containing ~50–70% grassland, abundance decreased more than threefold if half the grassland area was near an edge, and the landscape contained trees. Effective conservation requires ensuring that habitat is suitable at spatial scales larger than that of the territory or home range. Protecting prairie remnants from agricultural conversion and woody encroachment, promoting CRP enrollment, and maintaining portions of undisturbed prairie in working rangelands each year are critical to protecting threatened grassland species. Both Henslow’s Sparrows and Grasshopper Sparrows were influenced by habitat fragmentation, underscoring the importance of landscape features in driving habitat selection by migratory birds. As habitat loss threatens animal populations worldwide, conservation efforts focused on protecting and restoring core habitat could help mitigate declines of sensitive species.
Keywords: Habitat loss; Habitat fragmentation; Matrix effects; Patch shape; Landscape pattern; Migratory birds